Krüppel Regulates Cell Cycle Exit and Limits Adult Neurogenesis of Mushroom Body Neural Progenitors in Drosophila - Chen, Dongni Shao; Man, Jin; Shu, Xian; Shi, Haoer; Xia, Xue; Abula, Yusanjiang; Kimata, Yuu (bioRxiv, 2025)
In many organisms, including Drosophila and humans, neural progenitors exit the cell cycle and are eliminated by the end of development, which retricts adult neurogenesis to specific brain regions such as the mammalian hippocampus. Here, we show that the conserved transcription factor Krüppel (Kr) regulates the proliferation and neurogenic capacity of mushroom body neuroblasts (MBNBs), which generate the learning and memory center in the Drosophila brain, functionally analogous to the hippocampus. Neuroblast-specific Kr RNAi and the Irregular facet (KrIf-1) mutation extends MBNB lifespan, enabling continued neurogenesis in the adult brain. Kr is expressed at low levels in postembryonic MBNBs, and its pupal stage-specific depletion is sufficient to induce MBNB retention, distinguishing this role from its established function in embryonic neurogenesis. Persisting MBNBs maintain expression of the RNA-binding protein IGF-2-binding protein (Imp), which promotes MBNB proliferation and early neuronal fate. Co-depletion of Imp abolishes extended neurogenesis induced by Kr depletion. Additionally, Krüppel homolog 1 (Kr-h1), another Kr family protein and a key regulator of hormone-mediated transcription, antagonises Kr’s function: its knockdown suppresses the Kr depletion phenotype while its overexpression drives tumour-like neuroblast overgrowths. These findings define a lineage-specific regulatory axis governing adult neurogenesis in Drosophila, with potential parallels in other organisms.